Wybrane tematy w praktyce nauczania komunikacji interkulturowej pomiędzy Polakami i Austriakami - Hofbauer, Helmut (Selected Topics in the Practice of Teaching Intercultural Communication between Austrians and Poles, 2008)
The paper concentrates on the description of the practice of teaching students Intercultural Communication and presents a number of subjects which turned out to be the most successful. The author describes his own experiences in conveying his knowledge about Austria, existing intercultural differences between Austria and Poland, as well as theory of Intercultural Communication to students of German Philology.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 223-232